Impacts of strigolactone on shoot branching under phosphate starvation in chrysanthemum (Dendranthema grandiflorum cv. Jinba) - Xi, Lin; Wen, Chao; Fang, Shuang; Chen, Xiaoli; Nie, Jing; Chu, Jinfang; Yuan, Cunquan; Yan, Cunyu; Ma, Nan; Zhao, Liangjun (Frontiers in Plant Science, 2015)
Chrysanthemum (Dendranthema grandiflorum cv. Jinba) shoot branching is determined by bud outgrowth during the vegetative growth stage. The degree of axillary bud outgrowth is highly influenced by environmental conditions, such as nutrient availability. Here, we demonstrated that phosphorus (Pi) starvation significantly reduces axillary bud outgrowth in chrysanthemum. A strigolactone (SL) biosynthesis gene, DgCCD7, was isolated and characterized as an ortholog of MAX3/DAD3/RMS5/D17. By using ultra-performance liquid chromatography coupled with mass spectrometry (UPLC-MS), three putative SLs were identified and detected strong induction under Pi starvation conditions. Determinations of the distribution of SLs and negative regulation of DgCCD7/8 time-course in root indicated systemic response of SL. However, temporal expression patterns of biosynthesis and signaling genes in nodes revealed that Pi starvation causes a local response of SL pathway. Application of modified node segments treated with or without auxin and Pi revealed that in the absence of exogenous auxin, Pi delay axillary buds outgrowth and up-regulating local SL pathway genes. These data indicate that an auxin-SL regulatory loop respond to Pi starvation for delaying bud outgrowth locally, root biosynthesized SLs are transported acropetally and function in shoot branching inhibition under Pi starvation. We propose that SLs contribute to chrysanthemum shoot branching control in response to Pi-limiting conditions in a systemic way.